O festejo da abolição, na comunidade quilombola dona Juscelina/Muricilândia-TO: o turismo cultural e patrimônio imaterial. - Borges, Arystóteles Franklyn Chaves (Universidade Federal do Tocantins, 2023)
In the production, process of this article entitled the celebration of the abolition in the Quilombola community Dona Juscelina / Muricilândia-To: cultural tourism and intangible heritage. It was sought to make a potential analysis of the Quilombola Dona Juscelina community for cultural tourism through the Abolition Celebration. In addition, the research had as specific objectives to investigate the representations of the intangible cultural heritage of the community, through the Abolition Celebration, and also to identify the perception of the organizers and masters of the cultural manifestations of the celebration, in relation to the quilombola identity. For the production of the present work, bibliographical researches were used, being mostly electronic and a small physical part. Field research was also used, where two questionnaire models were used, one of them being the IPHAN Participatory Inventory celebrations, and a questionnaire with semi-structured questions to achieve the research objectives. As a result, it was overified that the Quilombola Dona Juscelina Community, through the Abolition Celebration has great potential for cultural tourism, since it is already possible to verify that tourism already exists in the community during the celebration.